Velocity and Pulsatility Measures in the Perforating Arteries of the Basal Ganglia at 3T MRI in Reference to 7T MRI - Arts, Tine; Meijs, Timion A.; Grotenhuis, Heynric; Voskuil, Michiel; Siero, Jeroen; Biessels, Geert Jan; Zwanenburg, Jaco (Frontiers in Neuroscience, 2021)
Cerebral perforating artery flow velocity and pulsatility can be measured using 7 tesla (T) MRI. Enabling these flow metrics on more widely available 3T systems would make them more employable. It is currently unknown whether these measurements can be performed at 3T MRI due to the lower SNR. Therefore, the aim of this study is to investigate if flow velocity and pulsatility in the perforating arteries of the basal ganglia (BG) can be measured at 3T MRI and assess the agreement with 7T MRI measurements as reference. Twenty-nine subjects were included, of which 14 patients with aorta coarctation (median age 29 years [21-72]) and 15 controls (median age 27 years [22-64]). Using a cardiac-gated 2D phase-contrast MRI sequence BG perforating arteries were imaged at 3T and 7T MRI and perforating artery density (Ndensity), flow velocity (Vmean) and pulsatility index (PI) were determined. Agreement between scanner modalities was assessed using correlation and difference plots with linear regression. A p-value≤0.05 indicated statistical significance. It was shown that perforating artery flow velocity and pulsatility can be measured at 3T MRI (Ndensity=0.21±0.11; Vmean=6.04±1.27; PI=0.49±0.19), although values differed from 7T MRI measurements (Ndensity=0.95±0.21; Vmean=3.89±0.56; PI=0.28±0.08). The number of detected arteries was lower at 3T (5±3) than 7T MRI (24±6), indicating that 3T MRI is on average a factor 4.8 less sensitive to detect cerebral perforating arteries. Comparison with 7T MRI as reference showed some agreement in Ndensity, but little to no agreement for Vmean and PI. Equalizing the modalities’ sensitivity by comparing the detected arteries on 7T MRI with the highest velocity with all vessels detected on 3T MRI, showed some improvement in agreement for PI, but not for Vmean. This study shows that it is possible to measure cerebral perforating artery flow velocity and pulsatility at 3T MRI, although an approximately fourfold sample size is needed at 3T relative to 7T MRI for a given effect size, and the measurements should be performed with equal scanner field strength and protocol.